PENGARUH TAYANGAN TELEVISI TERHADAP TINGKAT PRESTASI BELAJAR ANAK KELAS V SD NEGERI 071162 ESIWA - Donasokhi Harefa (Universitas Dharmawangsa, 2021)
The research aims to determine the effect of television broadcasts on the learning achievement level of fifth grade SD Negeri 071162 Esiwa children. This research was conducted at SD Negeri 071162 Esiwa in January 2019 until the end of April 2019. The samples in this study were all students of Class V SD Negeri 071162 Esiwa with a total of 40 people. The independent variable of concern in this study is television, while the dependent variable is learning achievement. To obtain material in this study, the authors chose a data collection tool, namely a questionnaire. Data analysis used simple linear regression analysis. The results showed that the product moment correlation test results showed that the effect of television shows had a positive and significant relationship to student achievement.